Implementation of Archive Training to Improve Official Administrative Document File Management Skills at SMA Nusa Bangsa Palembang - Zet Abdullah; Hendra Prasetyo; Fartina Destikarini; Nyimas Maynisa Aulia; Serey Mardy (Indonesian Journal of Community Engagement, 2026)
The development of digital administration requires schools to manage official documents in a more systematic, secure, and retrievable manner. Documents such as incoming letters, outgoing letters, student records, teacher files, activity reports, financial documents, and accreditation-supporting files need clear archive management procedures to prevent loss, misplacement, and retrieval difficulties. This community service activity aimed to improve participants’ understanding of official administrative document file management through archive training at SMA Nusa Bangsa Palembang. The activity was conducted on Saturday, 16 May 2026, starting at 08.00 WIB, and was attended by 13 participants consisting of students, school representatives, university students, and lecturers as the mentoring team. The method used a descriptive community service approach through several stages, including the introduction of archive concepts, official document classification, file naming standards, digital folder structure, document storage, data backup, and document retrieval simulation. The data were collected through attendance records, observation, documentation, and review of practice-based activities. The results showed that the archive training provided participants with practical understanding of how to manage school administrative documents more systematically. The activity also produced examples of document categories, folder structures, and file naming formats that can be used as references for managing official school documents. Therefore, archive training can be considered a simple and applicable strategy to support school administration, improve document retrieval, and strengthen archive management readiness in the school environment.